Technical oral presentations in English: Qualitative analysis of Malaysian engineering undergraduates' sources of anxiety - Noor Raha, Mohd Radzuan; Kaur, Sarjit (Elsevier, 2011)
Technical oral presentations are an integral component of engineering courses, but it is no doubt an anxiety-inducing experience for most engineering students. This paper presents an in-depth qualitative analysis of the sources for anxiety experienced by engineering students in delivering Undergraduate Research Project (URP) oral presentations. The URP oral presentations which are required to be delivered in English are part of faculty graduation requirements. Utilizing a qualitative method of enquiry, focus group interviews were conducted with 6 groups of students, comprising 44 final year engineering students from the Faculty of Chemical and Natural Resources Engineering at Universiti Malaysia Pahang, Malaysia. The interviews were conducted after they had completed the URP oral presentations in the 7th semester of their course of study. The results of the study reveal several main sources of anxiety that exist among the students in delivering the presentations, namely demanding and provocative evaluation panels, limited technical knowledge and barriers in students’ English language proficiency. The current findings add substantially to our understanding of contributory factors for anxiety feelings experienced by engineering students in delivering technical oral presentations in English. In addition, the findings have a number of important implications for future practice especially in the decision of the appropriate approach in managing anxiety in students’ presentations towards enhancing their presentation performance. The implications of this study point to the fact that providing for effective technical oral presentations in academic settings is an integral task for students’ preparation for future work-related tasks in their professional setting in today's globalised work environments.